CULTURA ORGANIZACIONAL GENERADA DE CERTIFICACIONES ISO 9001:2008, NMX-SAST- 001, NMX-SAA-14001 / ISO 14001, EN EMPRESAS DEL SECTOR SERVICIOS DE LA CONSTRUCCIÓN, MANTENIMIENTO E INSTALACIONES - Pineda, Lourdes del Carmen; Cerón, Marco Tulio; Pico, Beatriz; González, Manuel (European Scientific Journal, ESJ, 2015)
In this research, the type of organizational culture (OC) common in the services sector of the construction, maintenance and facilities are analyzed. This OC is ISO 9001: 2008, NMX-SAST-001, NMX-SAA-14001 / ISO 14001. We had ICACSA PROJECTS Company, service provider to understand and improve their performance. This performance was observed from the perspective of the design strategy of the organization. The research conducted in this study was descriptive and not a quantitative experimental transactional approach. We Denison, Lineberry and Carlton reference models for the evaluation of the OC. This selection was made in connection with the performance, culture and strategic alignment. We apply a diagnostic tool 45 questions to a sample of 75% of the 98 workers who are regularly on the central facilities of the company. We designed based on the Likert scale 5. The results show that the company has a mix of innovative and collaborative culture generated certifications described above questionnaire.